PENGARUH BENTUK PENAMPANG SEKSIONAL DEK JEMBATAN BENTANG PANJANG TERHADAP ANALISIS KECEPATAN KRITIS FLUTTER - Angga Dwi Saputra; Leonardo Gunawan; Rianto Adhy S; Mahesa Akbar (Jurnal Jalan-Jembatan, 2022)
Flutter is one of the most notable aeroelastic phenomenons in long-span bridges and needs to be evaluated carefully in the design phase as it might cause catastrophic structural failure. Numerical and experimental methods can investigate flutter on a deck bridge. However, the numerical methods could be less accurate for a complex-shaped deck, such as a deck equipped with railings and bluff cross-section bridges. Therefore, experimental methods using wind tunnels are more convenient for validating the flutter phenomenon on a bridge deck. The study was conducted to understand the effects of long-span bridge cross-section shape on the critical flutter speed analysis. The method is a hybrid numerical procedure, combining a wind tunnel test to identify the flutter derivatives coefficients and a numerical method to determine the critical flutter speed limit. The testing method developed in this research was used for both torsional and coupled–flutter cases. In the case of Testing Model I (thin plate), the developed method predicted the critical flutter speed of 16.7 m/s, which is close to the theoretical calculation using the thin-plate approach of 18.04 m/s. While in the case of testing model II (bluff body), the predicted flutter speed is 14.8 m/s which is close to the experiment result of 15 m/s. In the study case of the First Tacoma Bridge, the developed method could accurately predict the critical flutter speed with an error of only 4.3%. Hence, according to the study, the developed analysis method can accurately predict the flutter speed for both torsional and coupled flutter. Keywords: bridge, aeroelastic, flutter, wind tunnel, numerical.